1998
DOI: 10.1111/1467-9213.00101
|View full text |Cite
|
Sign up to set email alerts
|

Self-Deception Needs No Explaining

Abstract: How can one deceive oneself if at the same time one knows the truth? The idea of such a thing has puzzled philosophers, and many philosophical efforts have been devoted to explaining the puzzle. Yet all such attempts have been misplaced. For in fact there is nothing distinctive about the way the mind works in self‐deception, nothing that needs special explaining. The perception of a puzzle arises from certain mistaken assumptions about how the mind works generally. Once this is explained, we see that the way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…The extant literature on self-deception reveals the enormously rich field of very diverse types of explanations and theories of self-deception. Self-deception is studied in philosophy and psychoanalysis, neuroscience and cognitive psychology; evolutionary and social psychology (Rorty, 1994;Fingarette, 1998Fingarette, , 2000Goleman, 1997;Mele, 2001;Vaillant, 2005;Festinger, 1957;Trivers, 2000;von Hippel and Trivers, 2011). However, interdisciplinary reviews of this literature are extremely rare (Fingarette, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The extant literature on self-deception reveals the enormously rich field of very diverse types of explanations and theories of self-deception. Self-deception is studied in philosophy and psychoanalysis, neuroscience and cognitive psychology; evolutionary and social psychology (Rorty, 1994;Fingarette, 1998Fingarette, , 2000Goleman, 1997;Mele, 2001;Vaillant, 2005;Festinger, 1957;Trivers, 2000;von Hippel and Trivers, 2011). However, interdisciplinary reviews of this literature are extremely rare (Fingarette, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“… As examples of the intentional approach, see Pears (), Davidson (), Talbott (), Fingarette (), Bermúdez ().…”
mentioning
confidence: 99%
“… Herbert Fingarette, for example, argues that the purported paradoxes are actually generated by a misconstrual of how our minds generally work, and that self‐deception is in fact “…as ordinary and familiar a kind of mental activity as one can imagine. The result is unusual, but the way it is managed needs no more explaining than any normal, familiar and everyday activity of the mind…” (289).…”
mentioning
confidence: 99%
“… William Whisner and Herbert Fingarette have also suggested that self‐deception can be driven by motivated (but not intentional) manipulation of attentional processes.…”
mentioning
confidence: 99%